The Biochemistry, Toxicology, and Uses of the Pharmacologically Active Phytochemicals: Alkaloids, Terpenes, Polyphenols, and Glycosides - Chinaza Godswill Awuchi (Journal of Food and Pharmaceutical Sciences, 2019)
The research focused on the biochemistry and the medicinal uses of alkaloids, terpenes,polyphenols, and glycosides. Several parts of plants such as bark, root, leaf, stem, etc. are being used torevert abnormalities back to normal, prevent illnesses, or allay symptoms. These plant parts containbioactive compounds such as terpenes, glycosides, polyphenols, and alkaloids. Alkaloids have a rangeof pharmacological activities such as antiasthma (e.g. ephedrine), anticancer (e.g. homoharringtonine),antimalarial (e.g. quinine). Other alkaloids possess stimulant (e.g. cocaine, caffeine, theobromine, nicotine)and psychotropic activities (e.g. psilocin), and have been widely used as recreational drugs orin entheogenic rituals. Alkaloids can be toxic too (e.g. tubocurarine, atropine). Although alkaloids act ondiverse metabolic systems in humans and animals, they almost uniformly induce a bitter taste. Thecharacteristics and number of the structures of phenol in polyphenols underlie the unique chemical,physical, and biological (metabolic, therapeutic, toxic, etc.) properties of specific members of the class;e.g. ellagitannin and tannic acid. Generally, foods often contain complex mixtures of polyphenols. Severalpolyphenolic extracts, such as from grape seeds, olive pulp, maritime pine bark, or grape skin, are sold asingredients for functional foods, cosmetics, and dietary supplements. Terpenoids and terpenes are theprimary components of the essential oils of most types of flowers plants. Essential oils are used widely asscents and fragrances in perfumery and also in traditional medicine, such as aromatherapy. Similarly,many plant glycosides are used as medicines. Amygdalin and laetrile (a synthetic derivative) wereinvestigated as potential drugs for cancer treatment and were promoted as alternative medicine;nevertheless, they are ineffective and dangerous. Pharmacologically active phytochemicals can haveuseful applications, as well as safety concerns.